Strategic analysis of process maturity and the adoption of the ISO 9004 standard: a theoretical proposal for the tempered glass sector (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2024)
The objective of this study was to propose theoretical reflections on the strategic analysis of the maturity of the processes and the implementation of the ISO 9004:2018 standard, as tools to offer the best quality of products and services that meet the demands of the market. tempered glass, responding to the complex scenarios present in Venezuela through standardization and quality management of its processes. The methodological orientation is located in a descriptive bibliographic study, where different literatures are consulted to develop theoretical guidelines on the use of the Capability Maturity Model (CMM) as a tool in the strategic analysis of internal conditions, and the guidelines of the ISO 9004:2018 standard that directs these companies towards sustained business quality. It is concluded that given the dynamics of these scenarios, quality management continues to be the best strategy to satisfy the needs of customers and stakeholders, supported by the application of tools such as the CMM to identify errors that must be resolved a priori and then implement strategic planning directed by the philosophy of continuous improvement described in this standard, in order to offer tempered glass with the thickness, perforations and types of hardware according to the use required by customers, which will allow them to improve their competitive position in this market.
Keywords: strategic analysis; process maturity; iso 9004:2018 standard; tempered glass sector